5. EXPERIMENTAL FIGHTER AIRCRAFT GROUND MANEUVER SIMULATION - Farida, Ida; Kukuh Prasetyo; Eka Irianto Bhiftime; Nick Holson Manggiring Silalahi; Ahmad Hasan Fauzi; Kurniawan; Tia Dikatama Tsania (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to explore and analyze various factors that affect groundmaneuvers on fighter aircraft, focusing on the steering system and landing gear design.Fighter aircraft, as a major component in military operations, must not only have optimal airmaneuverability, but also be able to maneuver on the ground effectively and efficiently. Theability to move quickly and precisely on the ground is essential. Precise ground maneuversnot only ensure the safety of the aircraft, but also affect operational efficiency and responsetime in dealing with emergency situations. In this study, simulations were conducted using amathematical model developed in MATLAB/Simulink software to model and analyze aircraftmovements during the ground operation phase. This model considers various importantparameters such as aircraft speed, nose landing gear deflection, and weight distributionsettings to obtain more accurate results. The results of this simulation show that changes inthe nose landing gear deflection affect aircraft movements, including the ability to changedirection with a smaller radius and shorter time. Thus, the results of this study are expectedto provide new insights into fighter aircraft design to improve ground maneuver performanceand improve fighter aircraft operational efficiency in various field conditions.